Interfaces between abusive use of psychoactive substances, presence of comorbidities, and suicide risk (Research, Society and Development, 2020)
We aimed to analyze suicide risk in psychoactive substances users through the presence of comorbidities. This is an exploratory-descriptive research with quantitative approach developed in a municipality of the 11th Health Regional of Ceará State. Instruments used for data collection were formulary for sociodemographic characterization, clinical aspects, and pattern of consumption; Patient Health Questionnaire (PHQ-9), and Suicide Risk Index (SRI). Results point out that most users 51,1% presents the F19 diagnosis, mental and behavioral disorders due to use of multiple psychoactive substances. In 24,4% was detected psychiatric comorbidities, and in 33,3% were identified clinical comorbidities. 55,6% of users presented depression episodes. As for the suicide risk index, 55,6% presented intermediate risk, and 20% high risk. The findings reinforce the importance of investigating psychiatric comorbidities presence in users of psychoactive substances, and its relationship with suicide risks. Such an evaluation will contribute to more effective interventions in the health care process.